Some conceptions of the superior normal course tutors in distance education mode about teaching geometry - Aldrin Cleyde da Cunha (Investigações em Ensino de Ciências, 2011)
This research investigated what are the conceptions that the Tutor of Distance Education has for the teaching of geometry in the Normal Course at Maringá State University. The hypothesis is that the conceptions of the Tutor has in relation to the subject and geometry may influence their behavior, their actions and consequently the process of teaching and learning. The research was carried out with 20 mathematics tutors from Maringá State University, the poles of Cianorte, Cidade Gaucha, Diamante do Norte, Goioerê, Paranavaí, Sarandi, from January 2009 to May 2009, after the end of the mathematics module. We applied an interview questionnaire for data collection. The answers were qualitatively and quantitatively analyzed using the methodology of the Collective Subject Discourse and the software qualiquantiSoft, 1º edition, 2004. The survey results indicate several points about what are the conceptions that the Distance Education Course tutor has in the field of Geometry and the analysis of these conceptions indicate important facts to be considered.